2001
DOI: 10.1002/ijc.1461
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lck-derived peptides capable of inducing HLA-A2-restricted and tumor-specific CTLs in cancer patients with distant metastases

Abstract: The Lck protein (p56 lck ), a src family tyrosine kinase essential for T cell development and function, is aberrantly expressed in various types of cancers. We revealed recently that Lck can be a tumor antigen recognized by HLA-A24-restricted and tumor-specific cytotoxic T lymphocytes (CTLs) of cancer patients with metastases. In this study, we tried to identify Lck-derived epitopes capable of inducing HLA-A2-restricted and tumor-specific CTLs in cancer patients. The tumor-infiltrating lymphocytes (TILs) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Although the repertoire of peptide speciWcity of TIL-derived T cell clones was wide (Table 3), including almost each of the diVerent GCAA peptides tested, those speciWc for peptides belonging to SART3 and lck cancer antigens were the majority, being 24 and 32, respectively. For this aspect, our results are in agrement with the data of previous studies, which reported that the host immune response to gastric cancer frequently target SART and lck tumor-associatedantigens [16,26,33,36].…”
Section: Discussionsupporting
confidence: 90%
“…Although the repertoire of peptide speciWcity of TIL-derived T cell clones was wide (Table 3), including almost each of the diVerent GCAA peptides tested, those speciWc for peptides belonging to SART3 and lck cancer antigens were the majority, being 24 and 32, respectively. For this aspect, our results are in agrement with the data of previous studies, which reported that the host immune response to gastric cancer frequently target SART and lck tumor-associatedantigens [16,26,33,36].…”
Section: Discussionsupporting
confidence: 90%
“…In combination with known Lck peptides for HLA-A2 þ or -A24 þ cancer patients Imai et al, 2001), those identified in the present study enable us to develop a peptidebased anti-cancer vaccine for cancer patients with metastases in diverse ethnic populations. % lysis * Figure 4 Peptide-specific cytotoxicity against cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…We previously reported that HLA-A24-restricted tumourreactive CTLs from patients with distant metastases can recognise Lck-derived peptides as a tumour antigen . We also identified Lck-derived peptides that were applicable to metastatic cancer patients positive for HLA-A2 molecules (Imai et al, 2001). Thereafter, we carried out peptide-based immunotherapy against various types of cancer in which Lck-derived peptides were vaccinated into HLA-A24 þ or -A2 þ cancer patients (Sato et al, 2003;Mine et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This patient received vaccination of the SART3 302-310, Lck 246-254, WHS 103-111 and HNR 140-148 peptides, and we have already reported that all of these peptides can be presented by HLA-A*0206 molecules. (22)(23)(24) We next examined whether or not personalized peptide vaccination in combination with TS-1 could augment peptide-specific CTL or IgG in patients after the sixth vaccination ( Table 1). The vaccination increased peptide-specific CTL response to two, three and one of the four vaccinated peptides in patients 1, 2 and 3, respectively, who had no CTL activity in prevaccination PBMC and received the vaccination combined with a maximum dose (80 mg/m 2 /day) of TS-1.…”
Section: Methodsmentioning
confidence: 99%